Let's consider five consecutive integers n−2, n−1, n, n+1, and n+2.
The sum of these integers is:
(n−2)+(n−1)+n+(n+1)+(n+2)=5n
So, the mean is:
5n5=n
Since n is an integer, the mean is always an integer.
CloseTo show that (3n−2)3+(3n+2)3=54n3+72n, we start by expanding each cube:
(3n−2)3=27n3−54n2+36n−8
(3n+2)3=27n3+54n2+36n+8
So, now we can add the two expressions:
(3n−2)3+(3n+2)3=54n3+72n
Thus, we have shown that:
(3n−2)3+(3n+2)3=54n3+72n
Closea)
We start with the given: (x+3)2=x2+6x+9.
Then, we multiply by (x+3):
(x+3)3=(x2+6x+9)(x+3)
Expand and combine like terms:
(x+3)3=x3+9x2+27x+27
b)
i. x=3
Direct calculation: (3+3)3=63=216
Substituting into the expanded form: 33+9∗32+27∗3+27=27+81+81+27=216
ii. x=−2
Direct calculation: (−2+3)3=13=1
Substituting into the expanded form: (−2)3+9⋅(−2)2+27⋅(−2)+27=−8+36−54+27=1
CloseWe can express any odd number in the form 2k+1, where k is an integer. So, let:
a=2m+1
b=2n+1
Where m and n are any integers.
The sum of a and b is:
a+b=(2m+1)+(2n+1)
a+b=2m+2n+2=2(m+n+1)
Since m+n+1 is an integer, it has to be even since it is multiplied by 2. Thus, a+b is an even number.
Closea)
16x2−44x2+6x+2=4x−2x+1
Numerator: 16x2−4=(4x−2)(4x+2)
Denominator: 4x2+6x+2=(4x+2)(x+1)
16x2−44x2+6x+2=(4x−2)(4x+2)(4x+2)(x+1)
So, we can cancel 4x+2 from numerator and denominator, which ultimately proves the initial expression:
16x2−44x2+6x+2=4x−2x+1
b)
We know that the denominator can't be equal to 0, so:
From the LHS: (4x+2)(x+1)≠0
From the RHS: (x+1)≠0
(4x+2)(x+1)≠0
(x+1)≠0
x≠−1, x≠−12
CloseLet's consider three consecutive integers n−1, n, and n+1. Their squares are:
(n−1)2,n2,(n+1)2
By expanding these, we get:
(n−1)2=n2−2n+1
n2
(n+1)2=n2+2n+1
The mean of these squares is:
(n2−2n+1)+n2+(n2+2n+1)3=3n2+23
3n2+23 is not an integer because 3n2+2 is not divisible by 3.
CloseSince the are two consecutive even integers, we know that b=a+2. So, the difference of their squares can be denoted as:
b2−a2
(a+2)2−a2=a2+4a+4−a2=4a+4=4(a+1)
As it can be noticed, a+1 is the value of the integer between them, since the first integer is a and the second one is a+2. Hence, we have proved that the difference between the squares is equal to 4 times the integer between a and b.
To prove the sum of cubes of two consecutive odd integers is divisible by 2, let the integers be 2n+1 and 2n+3.
Their cubes are: (2n+1)3 and (2n+3)3. Let's now expand them:
(2n+1)3=8n3+12n2+6n+1
(2n+3)3=8n3+8n3+36n2+54n+27
By summing them up we have:
(2n+1)3+(2n+3)3=16n3+48n2+60n+28
Factoring out 2:
2(8n3+24n2+30n+14)
Hence, the sum is divisible by 2.
CloseTo show that 3√2−5 is irrational, we will use a proof by contradiction.
Suppose 3√2−5 is rational. Then, there exist integers a and b (with b≠0) such that:
3√2−5=ab
Rearrange the equation to solve for √2:
3√2=ab+5
3√2=a+5bb
√2=a+5b3b
The right-hand side of the equation, a+5b3b, is a rational number because a, b, and 5b are integers, and 3b≠0. However, √2 is known to be irrational. This leads to a contradiction because a rational number cannot equal an irrational number.
Since our assumption that 3√2−5 is rational leads to a contradiction, 3√2−5 must be irrational.
CloseTo prove that n3+2n is a multiple of 3 for any integer n, we will use a direct proof.
Any integer n can be expressed in one of the following forms:
where k is an integer.
Case 1: n=3k
n3+2n=(3k)3+2(3k)=27k3+6k=3(9k3+2k)
This is clearly a multiple of 3.
Case 2: n=3k+1
n3+2n=(3k+1)3+2(3k+1)
Expand (3k+1)3:
(3k+1)3=27k3+27k2+9k+1
Thus:
n3+2n=27k3+27k2+9k+1+6k+2=27k3+27k2+15k+3=3(9k3+9k2+5k+1)
This is a multiple of 3.
Case 3: n=3k+2
n3+2n=(3k+2)3+2(3k+2)
Expand (3k+2)3:
(3k+2)3=27k3+54k2+36k+8
Thus:
n3+2n=27k3+54k2+36k+8+6k+4=27k3+54k2+42k+12=3(9k3+18k2+14k+4)
This is a multiple of 3.
In all cases, n3+2n is a multiple of 3. Therefore, n3+2n is a multiple of 3 for any integer n.
CloseProve true for n=1:
1∑r=1r3=13=1
The right-hand side of the formula is:
(1(1+1)2)2=(22)2=12=1
Thus, the formula holds for n=1.
Assume that the formula holds for some positive integer k, i.e.,
k∑r=1r3=(k(k+1)2)2
We need to show that the formula holds for k+1, i.e.,
k+1∑r=1r3=((k+1)(k+2)2)2
Start with the left-hand side:
k+1∑r=1r3=k∑r=1r3+(k+1)3
Using the inductive hypothesis:
k+1∑r=1r3=(k(k+1)2)2+(k+1)3
Simplify the expression:
=k2(k+1)24+(k+1)3
Factor out (k+1)2:
=(k+1)2(k24+(k+1))
Combine the terms inside the parentheses:
=(k+1)2(k2+4(k+1)4)=(k+1)2(k2+4k+44)
Factor the numerator:
=(k+1)2((k+2)24)=((k+1)(k+2)2)2
Thus, the formula holds for k+1.
By the principle of mathematical induction, the formula
n∑r=1r3=(n(n+1)2)2
holds for all positive integers n.
Close